2019
DOI: 10.2166/wh.2019.288
|View full text |Cite
|
Sign up to set email alerts
|

Virulence determinants in genetically heterogeneous populations of Aeromonads recovered from an urban lagoon

Abstract: The diversity and distribution of Aeromonas spp. associated with virulence profiles from the Rodrigo de Freitas Lagoon were investigated using phylogenetic analysis of gyrB/rpoB gene sequences for speciation. The concatenated gyrB/rpoB gene sequences clustered into five species: Aeromonas punctata/caviae (n ¼ 37), A. hydrophila (n ¼ 10), A. dhakensis (n ¼ 16), A. jandaei (n ¼ 1) andA. enteropelogenes/trota (n ¼ 3). The virulence genes (atc/aerA/hlyA/asp/amp) resulted in 19 virulence profiles, distributed heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Indeed, several studies have already reported the transport of ARGs, antimicrobial residues, heavy metals, and other pollutants in this kind of effluent [10,19]. Hence, the isolation of antimicrobial and heavy metal-resistant Aeromonas strains in a recreational environment raises attention to the potential risks associated with human exposure to these waters or the consumption of seafood from this region [20,21]. Although cases of Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have already reported the transport of ARGs, antimicrobial residues, heavy metals, and other pollutants in this kind of effluent [10,19]. Hence, the isolation of antimicrobial and heavy metal-resistant Aeromonas strains in a recreational environment raises attention to the potential risks associated with human exposure to these waters or the consumption of seafood from this region [20,21]. Although cases of Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to infecting fish and humans, A. dhakensis isolates have been cultivated from marine mammals [ 18 , 19 ], rodents [ 20 , 21 ], reptiles [ 22 , 23 ] and invertebrates [ 24 , 25 , 26 ]. Moreover, microbiological screens have detected A. dhakensis in otherwise healthy populations of fish [ 7 ] and people [ 27 ], various aquatic environments including river water [ 28 , 29 ], lagoons [ 30 ], drinking water [ 31 ] and wells [ 32 ], as well as sewage [ 33 ] and foodstuffs [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%